Disiplin Gereja sebagai Sarana Pemulihan Relasi Sosial dan Penggerak Partisipasi Jemaat dalam Misi (International Forum of Researchers and Lecturers, 2025)
This article examines the importance of understanding and applying church discipline in the life of today’s congregation based on biblical principles. Church discipline is not merely seen as a form of punishment but as a means of God's grace to bring about restoration, spiritual growth, and order within the body of Christ. Through the study of Scripture and theological reflection, this paper explains that discipline is an expression of God’s love aimed at guiding His people toward repentance and truth. In practice, discipline must be carried out with love, patience, and wisdom, thus reflecting the character of Christ rather than serving merely as a corrective measure. The article also highlights the challenges of applying church discipline in the context of a modern culture that tends to reject authority and correction. Nevertheless, the author asserts that discipline remains relevant and essential as a means of preserving the holiness of the church and its witness to the world. The conclusion of this discussion shows that church discipline, when properly implemented, has a positive impact on both individuals and the faith community as a whole.